A theoretical investigation of size-dependent composition and stresses in nanowires and nanotubes of ceria. (15th March 2016) - Haftbaradaran, Hamed; Mossaiby, Farshid
Abstract: In the past few decades, nanostructures of ceria have received significant attention for potential applications in a variety of technologies. Experiments have frequently shown that physical properties of ceria nanomaterials are strongly size-dependent. Here, by accounting for the highly non-linear coupling between electrical, chemical and mechanical driving forces, we develop a continuum model which allows us to investigate equilibrium distribution of defects in nanowires and nanotubes of ceria. It is shown that the model predicts strongly size-dependent non-stoichiometric composition, lattice constant and surface stresses in ceria nanostructures whose diameter is comparable with the Debye's length scale of the problem. Graphical abstract: